Familial Dyskeratotic Comedones: A Case Report and Literature Review - Tejapira K; Suchonwanit P (Dove Medical Press, 2023)
Kasama Tejapira, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat Suchonwanit, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 ext 4, Email poonkiat@hotmail.comAbstract: Familial dyskeratotic comedones (FDC) is an autosomal dominant inherited skin disorder characterized by generalized multiple discrete comedone-like hyperkeratotic papules. The disease demonstrates a distinct histopathologic feature of dyskeratosis of the crater-like invaginated epidermis or follicle-like structures with or without acantholysis. Despite its asymptomatic and benign course, the condition is refractory to treatment. Herein, we report a case of a 54-year-old female presenting with progressively developed generalized multiple hyperkeratotic papules with central keratin plugs on the trunk and extremities for 20 years. A definite diagnosis was made by clinical manifestations and histopathological examination. The lesions were slightly improved after 3 months of topical retinoids and urea cream treatments. Besides, we first describe dermoscopic findings of FDC and reviewed 21 previously reported FDC cases from 11 families in the literature.Keywords: acne, autosomal dominant, comedone-like lesions, dermoscopy, dyskeratosis, hyperkeratosis